2018
DOI: 10.1080/09712119.2018.1450752
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perception of drought and its socioeconomic impact: the case of Tigray and Afar regions of Ethiopia

Abstract: A cross-sectional study was conducted from March 2016 to June 2016 to assess the perception of farmers on drought and its socioeconomic impact, and their mitigation and adaptation strategies. A total of 240 respondents from three districts in Tigray and one district from Afar were considered. The study indicated a significant reduction in the farm income (from 21,882 to 6482 ETB) and income from the livestock sector (12,833 to 5659 ETB). The average market price of cattle has reduced from 8228 to 4096 ETB due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
2
12
1
Order By: Relevance
“…A majority of respondents have stated that drought has become more frequent over the past 20 years. This has been confirmed in several studies (Chauhan and Ghosh, 2014; Martin et al, 2016; Menghistu et al, 2018; Udmale et al, 2014) which stated that the frequency, duration, severity and occurrence of drought is increasing due to the impacts of climate change. Furthermore, climate projections have predicted that annual air temperatures are estimated to increase within the range of 1.1–6.4°C by the year 2050 (Menghistu et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A majority of respondents have stated that drought has become more frequent over the past 20 years. This has been confirmed in several studies (Chauhan and Ghosh, 2014; Martin et al, 2016; Menghistu et al, 2018; Udmale et al, 2014) which stated that the frequency, duration, severity and occurrence of drought is increasing due to the impacts of climate change. Furthermore, climate projections have predicted that annual air temperatures are estimated to increase within the range of 1.1–6.4°C by the year 2050 (Menghistu et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…Farmer’s perceptions of drought have an influence on the way they choose to respond to it. Studies conducted by Menghistu et al (2018), Udmale et al (2014) and Mertz et al (2009) revealed that African farmers are capable of understanding their climate and recognizing environmental change. Studies regarding farming adaptation to climate change (Deressa et al, 2010; Eriksen and Low, 2005; Slegers, 2008) have shown that perceptions of African farmers have guided innovation, choice and use of indigenous adaptation strategies with great success.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, perceptions of households with differential characteristics are also genuine in Southern Ethiopian lowlands where households expressed their perceptions for local climate variability related interrogations as good times only remained as past history, rainfall both in its amount and frequency (rainy days) has been observed with decreasing tendency, and bad weathers are the implications of God's punishment (Aklilu and Alebachew 2009). Ethiopian farmers perceive drought impacts as augmenting average temperature and degraded environmental resources like water quality, pasture, and forest at a maximum extent with meager proactive preparedness on the contrary (Habtamu et al 2018). These conditions further necessitate vitally investigating local communities' perceptions and understanding of climate induced health hazards for effective disaster risk management (Ncube and Tawodzera 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The study examined socioeconomic and environmental impacts, adaptation strategies, and opinions on government drought mitigation measures. A recent study by Menghistu et al. (2018) assessed farmers' perception of drought and its impact in Tigray.…”
Section: Introductionmentioning
confidence: 99%